Effects of native plants and IGRs on the development of Tetranychus urticae Koch (Acari: Tetranychidae) - Naher, N; Islam, T; Haque, MM; Parween, S (University Journal of Zoology, Rajshahi University, 2007)
Effect of the seed dust of yellow karavi (Nerium oleander L.), flower juice of akanda (Calotropis procera L.) and two IGRs (diflubenzuron and triflumeron) were observed on the development of two-spotted spider mite (TSSM), Tetranychus urticae Koch. The seed dust of yellow karavi and akanda juice delayed the development of T. urticae resulting the elongation of duration of different developmental periods. But, the last stage of development was not affected with these treatments. Similarly, the two IGRs also significantly extended the duration of different developmental stages except deutonymph to adult. The different doses of two plant materials and two IGRs produced different effects on the development of two-spotted spider mite. Key words: Tetranychus urticae, Calotropis procera, Nerium oleander, diflubenzuron, triflumuron, developmental period Univ. j. zool. Rajshahi Univ. Vol.25 2006 p.18-22